Analisis Pengembangan Produk Tongkat Lansia - Jihan Fildzah Yustia; Raghdawulan Raghdawulan; Saddam Ridwan; Sofyan Maulana; Vika Restianti; Niken Parwati (JURNAL Al-AZHAR INDONESIA SERI SAINS DAN TEKNOLOGI, 2021)
The aging process brings various consequences in the form of physical, mental, and social problems so that an elderly person experiences limitations. The limitations of the elderly in carrying out their activities, especially in foot movement when walking, therefore a walking aid is needed. Each walking aid has a different function and usage method, one of which is a cane. Canes are often used to help balance, widen the stride and lower the weight on the legs. Safe and comfortable use is essential for the cane to function properly in assisting walking function. Canes still do not have a new design that suits the needs of the elderly. In this study, the development of a cane product for the elderly was carried out which was adapted to the ergonomic aspects and ideal aesthetic aspects. The aim is to provide convenience for the elderly in carrying out activities despite their limitations. Based on the research of the report on product development, namely Tongkat Wusaji using the Garvin Dimension method which is supported by 5 parts, namely performance, durability, features, serviceability, and aesthetics. It was found that the product concept applied to the Wusaji Stick uses aluminum material which has a product resistance of more than 3 years. The Wusaji stick has a minimalist design that is supported by the Bfinders and auto adjustable features and there are ergonomic usage procedures. Tongkat Wusaji has a product selling price of Rp. 250,000.Keywords: Identify customer needs, Product development, Product specifications, Industrial design